Psychological Capital sebagai Mediator Hubungan Kepemimpinan Transformasional dengan Kesiapan untuk Berubah Karyawan - Hana Riyandika Rohimatuzahroh; Kristina Haryanti (Jurnal Ilmiah Psikologi MIND SET, 2023)
Change has become an inevitable issue for a company to keep growing. For the success of the change process, the individual and company must be aware of the change and the will to change. This research aimed to focus on the role of Psychological Capital as the mediator variable of transformational leadership relationship with readiness to change in employees. The respondents in this research were 165 employees of a manufacturing company in Kudus. The data were obtained from the readiness to change scale, Psychological Capital adapted back translation, and the transformational leadership scale created by the researcher. This study used mediator analysis with the help of the JASP 0.16.1.0 program. The results of this research indicated that Psychological Capital mediated the relationship between transformational leadership and readiness to change in employees.